Arithmetics and Politics of Domestic Resource Mobilization - Bolch, Kimberly B. (World Bank, Washington, DC, 2017)
The 2015 United Nations resolution on Financing for Development stresses the importance of effective resource mobilization and use of domestic resources to pursue sustainable development. The first Sustainable Development Goal is to eradicate extreme poverty for all people everywhere by 2030. This paper proposes an accounting exercise to assess whether it is feasible for countries to eliminate poverty using only domestic resources, in other words, by mere redistribution. Moreover, the paper argues that the concentration of resources in the hands of fewer individuals in the society may hinder the feasibility of implementing effective fiscal policies (from the revenue side and the social spending side) to reduce poverty. The paper provides a new tool to assess the capacity of countries to eliminate poverty through redistribution, and a new tool to approximate the concentration of political influence in a country. The new methodologies are applied to the most recent surveys available for more than 120 developing countries. The findings show that countries with the same fiscal capacity to mobilize resources for poverty eradication differ widely in the political feasibility of such redistribution policies.